Metal‐Free Reductive Cleavage of CN and SN Bonds by Photoactivated Electron Transfer from a Neutral Organic Donor1. (6th December 2013) - O'Sullivan, Steven; Doni, Eswararao; Tuttle, Tell; Murphy, John A.
Abstract A photoactivated neutral organic super electron donor cleaves challenging arenesulfonamides derived from dialkylamines at room temperature. It also cleaves a) ArCNR and b) ArNC bonds. This study also highlights the assistance given to these cleavage reactions by the groups attached to N in (a) and to C in (b), by lowering LUMO energies and by stabilizing the products of fragmentation.